PERSPEKTIF KAJIAN AKSIOLOGI PADA PEMBELAJARAN DARING DI ERA PANDEMIC - Anim Anim; Dian Armanto; Nilam Sari (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2021)
Technological progress should contribute many benefits to human welfare, especially in the education aspect. In the pandemic era, teachers are forced to be technology literate by implementing online learning. However, in reality, the use of technology in online learning becomes an obstacle because optimal learning is not achieved specifically as the government hopes. This study discusses the analysis of axiology in online learning and uses the analysis method of literature review (literature research) from several relevant sources. The purpose of this article is to provide additional knowledge and learning for teachers so that later in the education unit they are able to actualize their abilities to produce competent students according to the expectations of the nation. The results of the literature study show that online learning does not support the achievement of learning aspects when viewed in axiological studies related to ethical and aesthetic values. Students still have difficulties and have problems in online learning so that they have not given birth to personal learning motivation and lack the creativity to develop the knowledge that has been obtained from teachers through online learning.Â Keyword: Axiology, Technology, Online Learning..